UJI ZAT PENGATUR TUMBUH DARI BERBAGAI JENIS DAN KONSENTRASI PADA STEK DAUN ILES-ILES (Amorphophallus muelleri Blume) - Sumarwoto Sumarwoto (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
This research was aimed  to test whether growth regulator substance could accelerate the growth of leaf cutting iles-iles and expected to be able to get the best type and concentration. The experiment was done on rainy season at experimental house, at 117  m sea level, with temperature average 27-32o C and rain fall about 1412 mm/year. The experiment was done using two factors with three replications using the Complettely Randomized Block Design. The level of kind growth regulator were three level (IAA (J1), IBA (J2), dan NAA (J3)), and concentration of growth regulator were four concentration (0 ppm (K0), 500 ppm (K1), 1000 ppm (K2), dan 1500 ppm (K3). The results showed that there was no interaction on type and concentration of growth regulator substance doses in affecting the growth plant vegetattif parameters. The using of growth regulator substance of resulted in the better viability and vigor of seeding 34% better than control (no growth regulator substance). The alternative  choice  growth regulator substance at first is IBA, whereas concentration of growth regulator substance on 1500 ppm